Sosialisasi dan Edukasi Menyikat Gigi bagi Siswa Kelas 1 SDN Karanganyar Kota Pasuruan - Ilmiyatul Rosidah; Galang Febriansyah; Ajijah Ajijah; Windy Legi Astutik; Dian Mu'alifah (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses socialization and education on toothbrushing for grade 1 students which was carried out in the context of Real Work Lectures (KKN) by PGRI Wiranegara University students at SDN Karanganyar, Pasuruan City. This program aims to increase awareness of dental and oral health in grade 1 students through educational activities and direct practice of correct tooth brushing. By actively involving students, this program provides an in-depth understanding of the importance of maintaining dental hygiene from an early age. The results of this activity show an increase in students' understanding of the importance of maintaining healthy teeth, as evidenced by changes in students' behavior in brushing their teeth. This article emphasizes the importance of dental health education interventions at the elementary school level to form healthy living habits.